Contraception use and its associated factors among grand multipara mothers in Kuantan - Che Abdullah, Che Azunie; Daud, Azlina; Ismail, Aisyah (2016)
Each pregnancy and childbirth brings a health risk for women, and the risk is magnified in women of high risk group especially for those in term of grand multipara women. With increasing numbers of grand multipara mother who would be facing greater reproductive risk as compared to healthy women, it would be important to have more information and better understanding on their reproductive health. Therefore, this study aimed to determine the contraceptives prevalence and to identify factors influencing contraceptive practices among grand multipara mothers in Kuantan. A descriptive cross sectional study were carried out in Klinik Kesihatan Ibu dan Anak Jaya Gading using purposive sampling and 49 of respondents has been selected as they fulfilled the criteria. This study found that the prevalence of contraceptive uses among grand multipara mothers is 51.0%. In addition, grand multiparas mothers who have high level of knowledge regarding contraceptive, positive attitude toward contraceptive practice and having discussion with spouse on contraception are more likely to use contraception in this study. There was no statistically significant difference between the practice of contraceptive use and occupation or number of living children. However, in this study we found a statistically significant association between the contraceptive practice and educational level of grand multipara mothers. As a conclusion, there is a knowledge / practice gap in the use of contraceptive. Awareness about contraceptive methods is high but multiple factors like fear of side effect, religious, and social factors affect the practice. Thus the results of the study provide some suggestions for improving the knowledge society towards good health and fertility potential trend towards the policy proposed by Malaysia's 70 million populations.